Effect of pruning intensity on growth, flowering, fruiting, yield and quality of ber cv. banarsi karaka - Ram, R.B.; Maurya, Divya; Lata, Rubee; Chaturvedi, Shashi Kant; Rao, Yashvant (Indian Journal of Agroforestry, 2020)
The present study was carried out at Horticultural Research Farm of Department of Applied Plant Science, (Horticulture) Babasaheb Bhimrao Ambedkar University, Vidya Vihar Rae Bareli Road, Lucknow during 2005-2006. Result revealed that 30 cm pruning intensity is useful for significantly improving, length of tertiary branches. Pruning intensity with 90 cm significantly increased, flowering, fruit set, fruit size and ascorbic acid whereas it reduced acidity.